A periodic bivariate integer-valued autoregressive model - Monteiro, Magda (2015)
In this paper, a bivariate integer-valued autoregressive model with periodic structure is introduced and studied in some detail. The model can be view as a generalization of the one considered in Pedeli and Karlis (2011) [Pedeli, X., Karlis, D., 2011. A bivariate INAR(1) process with application. Statist. Model. 11, 325– 349]. Emphasis is placed on models with periodic bivariate Poisson innovations. Basic probabilistic and statistical properties of the model are discussed. Moreover, parameter estimation and forecasting are also addressed.